Advances in Information Systems Third International Conference, ADVIS 2004, Izmir, Turkey, October 20-22, 2004. Proceedings - Yakhno, Tatyana; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2005)
This volume contains the proceedings of the 3rd International Conference on AdvancesinInformationSystems(ADVIS)heldinIzmir,Turkey,20–22October, 2004. This was the third conference dedicated to the memory of Prof. Esen Ozkarahan. We are very proud to continue this tradition and keep the memory of this outstanding scientist. The third conference covered many of the topics of the second one: databases and data warehouses, information systems development and management, - formation retrieval, distributed and parallel data processing, and evolutionary algorithms. Besides them some of the hot topics related to information systems were included in the scope of this conference, such as data mining and kno- edge discovery, Web information systems development, information privacy and security, multimedia information systems, and network management. This year we received 203 submissions from which the Program Committee selected 61 papers for presentation at the conference. The success of the conference was dependent upon the hard work of a large number of people. We gratefully acknowledge the contribution of the members of the Program Committee who did their best to review all submitted papers. We also thank all the specialists who helped us in reviewing the papers. We appreciated the constant support and help from the Rector of Dokuz Eylul University, Prof. Dr. Emin Alici. I would like to express my personal gratitude to Natalya Cheremnykh and Olga Drobyshevich for their help in producing the camera-ready version of these proceedings.
Databases and Data Warehouses -- Temporality in Databases -- On Uncertainty and Data-Warehouse Design -- A Data Warehouse Engineering Process -- Aggregation and Analysis of Spatial Data by Means of Materialized Aggregation Tree -- An Object-Oriented Framework for Reconciliation and Extraction in Heterogeneous Data Federations -- On Optimising Data Access Via Materialised Methods in Object-Oriented Systems -- Some Modifications of Bucket-Based Algorithms for Query Rewriting Using Views -- Data Mining and Knowledge Discovery -- A Data Mining Application on Air Temperature Database -- Incremental Association Rule Mining Using Materialized Data Mining Views -- Outlier Effects on Databases -- Finding Maximal Similar Paths Between XML Documents Using Sequential Patterns -- Web Information Systems Development -- Using Ontologies for Collaborative Information Management: Some Challenges and Ideas -- The Construction of Domain Ontology and Its Application to Document Retrieval -- WetDL: A Web Information Extraction Language -- Towards Building Knowledge Centres on the World Wide Web -- Navigation Modelling from a User Services Oriented Approach -- Kreios: Towards Semantic Interoperable Systems -- Adaptive Architecture for Web Server Survivability -- Information Systems Development and Management -- Integration and Maintenance of Heterogeneous Applications and Data Structures -- A Component Language for Hybrid Solver Cooperations -- Non-interleaved Quadtree Node Codification -- Parameterized Formatting of an XML Document by XSL Rules -- A Middleware Approach to Storing and Querying XML Documents in Relational Databases -- Information Retrieval -- On Families of New Adaptive Compression Algorithms Suitable for Time-Varying Source Data -- Text Summarization and Singular Value Decomposition -- Sentence Boundary Detection in Turkish -- Multiple Sets of Rules for Text Categorization -- Zipf’s Law and Mandelbrot’s Constants for Turkish Language Using Turkish Corpus (TurCo) -- Letter Based Text Scoring Method for Language Identification -- Parallel and Distributed Data Processing -- Parallel Implementation of a VQ-Based Text-Independent Speaker Identification -- A Distributed Model of Neuronal Regulators Based on Message-Driven Software Component Architecture -- Winsim: A Tool for Performance Evaluation of Parallel and Distributed Systems -- Integrating Distributed Composite Objects into Java Environment -- Content-Based Distribution for Load Sharing in Locally Clustered Web Servers -- A Study on Grid Partition for Declustering High-Dimensional Data -- Design and Implementation of a Real-Time Static Locking Protocol for Main-Memory Database Systems -- Multimedia Information Systems -- Integrated Querying of Images by Color, Shape, and Texture Content of Salient Objects -- Trajectory-Based Video Retrieval for Multimedia Information Systems -- Using an Exact Radial Basis Function Artificial Neural Network for Impulsive Noise Suppression from Highly Distorted Image Databases -- A Histogram Smoothing Method for Digital Subtraction Radiography -- Efficient Liver Segmentation Based on the Spine -- Information Privacy and Security -- Practical and Secure E-Mail System (PractiSES) -- A Preprocessor Adding Security to and Improving the Performances of Arithmetic and Huffman Codings -- Performance Evaluation of Digital Audio Watermarking Techniques Designed in Time, Frequency and Cepstrum Domains -- Evolutionary and Knowledge-Based Systems -- A Hybrid Genetic Algorithm for Packing in 3D with Deepest Bottom Left with Fill Method -- Multi-objective Genetic Algorithm Based Clustering Approach and Its Application to Gene Expression Data -- An Application of Support Vector Machine in Bioinformatics: Automated Recognition of Epileptiform Patterns in EEG Using SVM Classifier Designed by a Perturbation Method -- Selection of Optimal Dimensionality Reduction Methods for Face Recognition Using Genetic Algorithms -- Performance Comparison of Genetic and Differential Evolution Algorithms for Digital FIR Filter Design -- Kidney Allocation Expert System with Case-Based Reasoning -- Software Engineering and Business Process Models -- Integrating AI and OR: An Industrial Engineering Perspective -- Framework for Knowledge-Based IS Engineering -- Modelling Variability in Requirements with Maps -- Kaliphimos: A Community-Based Peer-to-Peer Group Management Scheme -- On the Application of WF-Nets for Checking Hybrid IDEF0-IDEF3 Business Process Models -- Practical Investigation into the Maintainability of Object-Oriented Systems for Mission Critical Business -- Network Management -- A New MAC Protocol Design for WATM Networks -- Fuzzy Logic Based Congestion Avoidance in TCP/AQM Networks -- Distributed Group Access Control Architecture for Secure Multicast -- Virtual-IP Zone Algorithm in IP Micro Mobility Environments -- A Network Management Approach for QoS Evaluation of IP Multimedia Services.
Keywords: Computers; Database management; Information storage and retrieval; Application software; Multimedia information systems; Artificial intelligence; Theory of Computation; Database Management; Information Storage and Retrieval; Information Systems Applications (incl. Internet).; Multimedia Information Systems; Artificial Intelligence